Compass - Comparative Literature in Africa : Essays in Honour of Willfried F. Feuser - Ekpo, Denis; Maduka, Chidi T.; Feuser, Willfried, 1928-2000 (Book collections on Project MUSE., 2016)
This is a commemorative volume devoted to the late Professor Willfried F. Feuser, a literary icon and a comparatist of no mean repute. Though German by origin, Professor Feuser showed great concern to the Africanist agenda of self-realisation, and therefore devoted the greatest part of his productive academic life to the cultural revival and socio-economic emancipation of Africa and the Diaspora through his scholarly publications. This book contains 20 essays on a wide range of issues in literary criticism.